Revitalizing Arabic Learning in Madrasah: A Deep Learning-Based Holistic Framework Integrating Islamic Pedagogy - Hania, Irfan; Ubaidillah, Ubaidillah; Mufrodi, Mufrodi; Faiqotussana, Faiqotussana; Rifaldi, Muhammad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study aims to formulate the